Anomalous right-sided pulmonary venous connection to the superior vena cava - Abbasi, Kiumars; Abbasi, Ali; Tazik, Mokhtar; Salehiomran, Abbas; Kazemisaeed, Ali; Sadeghian, Hakimeh (Monaldi Archives for Chest Disease, 2016)
Over the years, different techniques have been introduced for the repair of sinus venosus atrial septal defect (ASD) with anomalous right-sided pulmonary venous connection to the superior vena cava. We report the case of a 9- year-old girl, who presented with dyspnea and peripheral cyanosis. Preoperative echocardiography and angiography findings suggested a partial anomalous pulmonary venous connection. On cardiopulmonary bypass, the ASD was dilated, and the anomalous pulmonary vein was anastomosed to the right atrium and redirected to the left atrium using an intraatrial baffle and a tube graft. The intraoperative and postoperative periods were uneventful, and the patient is currently in good health at 4.5 years’ follow-up.